2017
DOI: 10.1371/journal.ppat.1006418
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional dissection reveals distinct roles of Ca2+-binding sites in the giant adhesin SiiE of Salmonella enterica

Abstract: The giant non-fimbrial adhesin SiiE of Salmonella enterica mediates the first contact to the apical site of epithelial cells and enables subsequent invasion. SiiE is a 595 kDa protein composed of 53 repetitive bacterial immunoglobulin (BIg) domains and the only known substrate of the SPI4-encoded type 1 secretion system (T1SS). The crystal structure of BIg50-52 of SiiE revealed two distinct Ca2+-binding sites per BIg domain formed by conserved aspartate or glutamate residues. In a mutational analysis Ca2+-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
(61 reference statements)
3
16
0
Order By: Relevance
“…In addition, MT measurements are done under exquisite control of force (force-clamp) and are stable over long time scales 21 . Still, the study of intact elastic proteins by single-molecule methods is limited due to the size of many of these proteins, ranging from 200 to 3700 kDa [22][23][24] , which is challenging to reach by heterologous protein expression systems 10,[25][26][27] . In addition, recombinant proteins do not contain native posttranslational modifications, which are key factors modulating the mechanical properties of proteins 28 .…”
mentioning
confidence: 99%
“…In addition, MT measurements are done under exquisite control of force (force-clamp) and are stable over long time scales 21 . Still, the study of intact elastic proteins by single-molecule methods is limited due to the size of many of these proteins, ranging from 200 to 3700 kDa [22][23][24] , which is challenging to reach by heterologous protein expression systems 10,[25][26][27] . In addition, recombinant proteins do not contain native posttranslational modifications, which are key factors modulating the mechanical properties of proteins 28 .…”
mentioning
confidence: 99%
“…The output topology and trajectory files were loaded into VMD to analyze the positions of the beta sandwiches relative to each other, and how this changed over time. To measure potential bending of the linker between the domains ( Peters et al, 2017 ), an oblique triangle was drawn between three atoms ( Mh Lap = Leu 240 Cβ – Val 247 Cβ – Ile 158 Cβ, Ah Lap = Ile 228 Cβ – Val 264 Cβ – Tyr 300 Cβ), and the obtuse angle was measured at each frame. To measure potential twisting of the linker between the domains, three lines were drawn between four atoms ( Mh Lap = Val 294 Cα – Leu 240 Cβ – Ile 158 Cβ – Ser 130 Cα, Ah Lap = Ile 334 Cα – Tyr 300 Cβ – Ile 228 Cβ – Glu 152 Cα), and the dihedral angle of the system was measured at each frame.…”
Section: Methodsmentioning
confidence: 99%
“…A similar calcium-dependent strategy has been recently discovered in bacterial adhesion proteins (adhesins). The extender beta sandwiches from an epithelial adhesin, SiiE, produced by Salmonella enterica require calcium for thermal stability and resistance to proteolysis ( Peters et al, 2017 ), while the massive ice-binding adhesion protein from the Antarctic bacterium Marinomonas primoryensis completely loses its tertiary structure in the absence of calcium ( Guo et al, 2013 ). Like cadherin, structure determination of small segments from both proteins showed the presence of calcium ions that coordinate to the linkers between beta-sandwich domains ( Griessl et al, 2013 , Vance et al, 2014 ), thereby producing a rod-like structure crucial for proper adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…A crystal structure of SiiE BIg50-52 provided insight into the BIg domain architecture and revealed two types of Ca 2+ -binding sites, which stabilize the rod-like structure [14]. Further studies showed that type I Ca 2+ -binding sites were essential for the efficient secretion of SiiE, whereas integrity of type II sites in the C-terminal portion was needed for mediating adhesion and invasion [15].…”
Section: Introductionmentioning
confidence: 99%